2017
DOI: 10.1038/s41562-017-0067
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neural characterization of optimistic reinforcement learning

Abstract: While forming and updating beliefs about future life outcomes, people tend to consider good news and to disregard bad news. This tendency is supposed to support the optimism bias. Whether this learning bias is specific to "high-level" abstract belief update or a particular expression of a more general "low-level" reinforcement learning process is unknown. Here we report evidence in favor of the second hypothesis. In a simple instrumental learning task, participants incorporated better-than-expected outcomes at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
267
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 220 publications
(309 citation statements)
references
References 49 publications
41
267
1
Order By: Relevance
“…Furthermore, participants showed no sign of leaky inference within each sequence, in either condition. The slower reversal learning in the outcome-based condition is also unlikely to arise from a biased, choice-supportive filtering of evidence described and reported across cognitive domains (Sharot et al, 2011;Bronfman et al, 2015;Lefebvre et al, 2017;Talluri et al, 2018;Yon et al, 2018). Indeed, the strength of conflicting evidence (inconsistent with beliefs) could be decoded with equal precision across conditions.…”
Section: Neural Dissociation Between Absolute and Relational Coding Omentioning
confidence: 82%
“…Furthermore, participants showed no sign of leaky inference within each sequence, in either condition. The slower reversal learning in the outcome-based condition is also unlikely to arise from a biased, choice-supportive filtering of evidence described and reported across cognitive domains (Sharot et al, 2011;Bronfman et al, 2015;Lefebvre et al, 2017;Talluri et al, 2018;Yon et al, 2018). Indeed, the strength of conflicting evidence (inconsistent with beliefs) could be decoded with equal precision across conditions.…”
Section: Neural Dissociation Between Absolute and Relational Coding Omentioning
confidence: 82%
“…While standard accounts of belief (or value) prescribe that an agent should learn equally well from positive and negative information (e.g., Barto and Sutton, 1998;Benjamin, 2018 for a review), previous studies have consistently shown that people exhibit valence-induced biases (e.g., Lefebvre et al, 2017;Kuzmanovic et al, 2018). These biases are traditionally exemplified in the so-called "good news/bad news" effect whereby people tend to overweight good news relative to bad news when updating self-relevant beliefs (Sharot and Garrett, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The development, adaptation and evolution of human social learning and cognitive skills in the economic environment is based on experiences acquired from environmental stimulus through time. These skills are crucial for setting perception, preferences and the decisionmaking process of humans interacting into the economic environment (Baker et al, 2017;Bechara and Damasio, 2005;de Bot et al, 2007;Frederick, 2005;Fryer and Jackson, 2003;Glowacki and Molleman, 2017;Kenrick et al, 2009;Lefebvre et al, 2017;Smith, 1991;Vriend, 1996).…”
Section: Resultsmentioning
confidence: 99%